2017
DOI: 10.1016/j.endm.2017.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Staircases, dominoes, and the growth rate of 1324-avoiders

Abstract: We establish a lower bound of 10.271 for the growth rate of the permutations avoiding 1324, and an upper bound of 13.5. This is done by first finding the precise growth rate of a subclass whose enumeration is related to West-2-stack-sortable permutations, and then combining copies of this subclass in particular ways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…For example, suppose H is the valid hook configuration of 21123214567 shown in Figure 6. Referring to the induced coloring shown in Figure 7, we find that (9,4), (10,5)…”
Section: Trees and Valid Hook Configurationsmentioning
confidence: 98%
“…For example, suppose H is the valid hook configuration of 21123214567 shown in Figure 6. Referring to the induced coloring shown in Figure 7, we find that (9,4), (10,5)…”
Section: Trees and Valid Hook Configurationsmentioning
confidence: 98%
“…The generating function for the last symmetry class, containing Av(1324) and Av(4231), remains unknown. Through about a dozen articles [8,25,28,29,36,37,64,66,67,95,117], the first fifty terms of the counting sequence of Av(1324) are known explicitly and rough bounds on the exponential growth are known.…”
Section: Enumeration Of Permutation Classesmentioning
confidence: 99%
“…For example, if π ∈ S n , then leg(π) = n+1 if and only if π avoids 231. The legal spaces of 145326 are (0, 1), (1,2), (4,5), (5,6), (6,7), so leg(145326) = 5. Imagine adding a new point somewhere to the left of all points in the plot of a permutation π.…”
Section: -Stack-sortable Permutationsmentioning
confidence: 99%
“…The articles [31] and [35] give different proofs that new combinatorial objects called "fighting fish" are counted by the numbers W 2 (n). The authors of [2] studied what they called "n-point dominoes," and they have found that there are W 2 (n + 1) such objects.…”
mentioning
confidence: 99%